Using biotechnology to solve engineering problems Non-destructive testing of microfabrication components - de Carvalho, Carla C. C. R. (2022)
Fundacao para a Ciencia e a Tecnologia, I.P. (FCT), Portugal, for financial support under program "Investigador FCT 2013" (IF/01203/2013/CP1163/CT0002) and UID/BIO/04565/2013. TS and RM acknowledge FCT for PEst-OE/EME/UI0667/2014 and UID/EMS/00667/2013. The study was also partially supported by project PTDC/EME-TME/118678/2010.